Assessment of Family Medicine Residents’ Perception about their Specialty and Residency Program in Iraq: Assessment of Family Medicine Residents’ Perception about their Specialty and Residency Program in Iraq - haikl, mais ahmed (Karbala Journal of Medicine, 2019)
Background: Family Medicine (FM) specialists are the frontline of medical services. So they require a wide range of knowledge, practice and experience. A periodic evaluation of family medicine residency training and the exploration of residents’ perception toward their specialty and training are important. Objective: To assess factors affecting clinical training of family medicine residents in training centers and evaluates their satisfaction about their training program. Subjects and methods: A cross sectional study was conducted covering several training centers in Iraq for the period of February 1 to July 31, 2018. A special self-administered questionnaire based on 5 points Likert scale prepared for this purpose and been tested by a pilot study. A total of 275 questionnaire paper distributed to family medicine residents. Results: The accomplished sample was 187 female represents 93% of them. Nearly 55% indicate that they if time is back they will choose FM again and similar percentage indicate that they will recommend FM to others. Nearly 75% of participants have positive feeling towards their future as family physicians. While 63.6% were dissatisfied with their residency training program. Lack of commitment of teaching hospitals to training curriculum, on different areas, and this indicate weak understanding and acceptance, to them and FM specialty from physicians of other clinical branches. Also they highlight that teaching hospitals is not committed to the training curriculum. Conclusion Family medicine residents still in favorite of their, but they have many critiques concerning their residency training curricula and the application clinical training in the hospitals. These points are vital, need to be considered by their supervisors and higher committees concerned.